Dziatki miłe Elżbiety i Stanisława Kruszyńskich - Żołądź-Strzelczyk, Dorota (Saeculum Christianum. Pismo Historyczne, 2019)
The article uses source materials to present the situation of the family of Stanisław Kazimierz Kruszyński, a noble living with his relatives in Lower Łąkta in Lesser Poland. The sylwa stored in the collection of Ossolineum in Wroclaw, contains several messages about children. These are notes speaking of the birth of subsequent children, the place and circumstances of their baptism. We also have a poem written by a mother after the death of her youngest children. And above all same, recommendations for the education of sons to be found in the will and the supplement to it. They had to study at the Piarist college in Podoliniec and then practice at the office. These few preserved sources provide us with information about family life and attitudes towards children in the early 18th century.